A hierarchical MoP nanoflake array supported on Ni foam : a bifunctional electrocatalyst for overall water splitting - Jiang, Yuanyuan (2020)
The search for an inexpensive bifunctional electrocatalyst for overall water splitting has attracted considerable research interest during the past years. Herein, self‐supported hierarchical electrodes comprising nickel foam (NF) and porous molybdenum phosphide (MoP) nanoflakes are fabricated by first growing MoO2 nanoflakes on Ni foam and then further phosphorization treatment. Remarkably, serving as both anode and cathode catalysts in a two‐electrode alkaline water‐electrolysis system, the designed electrodes only require a potential of 1.62 V to deliver a current density of 10 mA cm−2. This performance is close to that of the noble‐metal‐based electrodes, that is, integrated RuO2/Ni foam and Ni foam supported Pt/C electrodes. The low cost, facile preparation method, and desirable performance make this MoP/NF electrode a potential electrocatalyst for overall water splitting.